The Effect Of The Use Of E-Filing, Understanding, And Awareness On Taxpayer Compliance At KPP Sukomanunggal Surabaya - Anastasia Cininta Puteri Panjaitan; Emmywati (Journal Informatic, Education and Management (JIEM), 2025)
This research analyzes the influence of e-filing utilization, taxation understanding, and taxpayer awareness on compliance levels at KPP Sukomanunggal Surabaya. The research methodology employed a quantitative approach with multiple regression analysis of 123 respondents selected through purposive sampling. The research instrument in the form of structured questionnaires met validity and reliability tests with Cronbach's Alpha values ranging from 0.860-0.880. Analysis results demonstrate that e-filing utilization has a dominant influence on taxpayer compliance with a beta coefficient of 0.600, followed by taxation awareness (0.185) and taxation understanding (0.176). The research model explains 88.6% of taxpayer compliance variance with an F-value of 308.190 (p<0.001). Findings indicate that taxation technology modernization through e-filing serves as the primary catalyst in enhancing compliance behavior. Integration of technological aspects, education, and moral consciousness development creates optimal synergy in taxation compliance management. Research implications emphasize the urgency of implementing holistic strategies that combine technological convenience with enhanced taxation literacy and civic responsibility internalization to create sustainable voluntary compliance.